Elevated Neutrophil-to-Lymphocyte Ratio Is Associated With Poor Outcomes for Melanoma Patients Treated With PD-1 Inhibitor or Chemotherapy in a Chinese Population - Qi, Yalong; Liao, Daixiang; Mei, Dinglian; Zhang, Yong; Liu, Yang (Frontiers in Oncology, 2020)
Background: Previous studies have suggested that elevated pre-treatment neutrophil-to-lymphocyte ratio (NLR) is associated with worse outcomes in patients with a variety of cancers. The purpose of this retrospective analysis is to investigate the prognostic value of NLR in a Chinese melanoma population. Methods: Melanoma patients were divided into two groups based on pre-treatment NLR value (≥3 vs <3). Cox proportional hazard regression analysis and Kaplan-Meier method were conducted to study the prognostic role of NLR on overall survival (OS) and progression free survival (PFS). Results: A total of 159 melanoma patients were included in this study, including 40 patients treated with PD-1 inhibitor and 119 patients treated with chemotherapy.In PD-1 inhibitor group, the median OS was 18.0 months in the low NLR subgroup and 5.6 months in the high NLR subgroup; the median PFS was 7.0 months and 2.2 months, respectively. In chemotherapy group, the median OS was 23.0 months in the low NLR group and 8.0 months in the high NLR group,and the median PFS was 9.0 months and 4.0 months, respectively. Multivariate analysis showed that NLR was significantly associated with OS and PFS in melanoma patients treated with either PD-1 inhibitor immunotherapy or chemotherapy. Conclusion: In Chinese population, elevated NLR was closely related to worse survival in patients with melanoma treated with either PD-1 inhibitor monotherapy or chemotherapy.